The growth performance of developing countries in the last thirty years: Who gained? - Who lost? - Horst Siebert (Kiel Institute for the World Economy (IfW), 2006)
This paper answers the question which developing countries have gained and which have lost in the international division of labor during the last thirty years. The indicators used are GDP per capita in constant purchasing power parity and relative distance to the United States. Nearly all developing countries have improved in absolute terms over the last thirty years; many, among them China and India with large populations, have also reduced their relative distance to the United States. The paper classifies developing countries and discusses impediments to economic development and core elements of a growth strategy.
Keywords: F; O; O40; N; 330; Growth; GDP per capita; Stages of development; Classification of developing countries; Newly industrializing countries; Economic development; Entwicklungskonvergenz; Sozialprodukt; Entwicklungsstufe; Wachstumspolitik; Entwicklungsstrategie; Erfolgsfaktor; Entwicklungsländer; Schwellenländer